2014
DOI: 10.1021/jp5062489
|View full text |Cite
|
Sign up to set email alerts
|

N2 Selectivity of NO Reduction by NH3 over MnOx–CeO2: Mechanism and Key Factors

Abstract: In this work, the novel relationships of N 2 selectivity of NO reduction over MnO x −CeO 2 with the gas hourly space velocity (i.e., GHSV) and the reactants' concentrations were discovered. Meanwhile, the mechanism of N 2 O formation during the low temperature selective catalytic reduction reaction (SCR) over MnO x −CeO 2 was studied using in situ DRIFTS study and the transient reaction study. N 2 O formation over MnO x −CeO 2 mainly resulted from the Eley−Rideal mechanism (i.e., the reaction between overactiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
125
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 95 publications
(130 citation statements)
references
References 27 publications
4
125
1
Order By: Relevance
“…As shown in Fig. 11, there was an excellent linear relationship between the rate of NO reduction and gaseous NO concentration, which was consistent with the hint of Equation 26. Meanwhile, the rate of N 2 O formation hardly varied after the increase of gaseous NO concentration (shown in Fig.…”
Section: Steady State Kinetic Studysupporting
confidence: 75%
See 2 more Smart Citations
“…As shown in Fig. 11, there was an excellent linear relationship between the rate of NO reduction and gaseous NO concentration, which was consistent with the hint of Equation 26. Meanwhile, the rate of N 2 O formation hardly varied after the increase of gaseous NO concentration (shown in Fig.…”
Section: Steady State Kinetic Studysupporting
confidence: 75%
“…Reactions 10 and 11) can be described as: (25) Our previous study demonstrated that NH 2 on the surface was independent of the concentrations of gaseous NO and NH 3 at the steady state [15,26], which was mainly related to k 9 , the concentrations of NH 3 adsorbed and M n+ on the surface (hinted by Equation 20).…”
Section: Steady State Kinetic Studymentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, optimal combinations of different metal oxides can usually exhibit better SCR efficiency and thermal stability than single oxides. Li et al reported that MnO x -CeO x can improve the SCR activity, H 2 O-resistance and stability by mixing MnO x with CeO 2 [1416]. Besides, they usually exhibit many interesting properties in energy conversion and storage, catalysis and adsorption [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Although some SCR catalysts for example Mn based catalysts can operate at low temperatures [7], they are extremely restricted in the application due to the higher N 2 O selectivity and the lower NO x conversion at high temperatures [8]. Therefore, there is a strong demand for the SCR catalysts with a broad temperature window [9].…”
Section: Introductionmentioning
confidence: 99%